Circular RNAs in Cervical Cancer: What are the Prospects? - S. A. Begliarzade; R. I. Tamrazov (Креативная хирургия и онкология)
C ervical cancer remains a pressing global health problem, creating a significant health burden for women worldwide. High incidence and mortality rates necessitate further research to unravel its underlying molecular mechanisms and identify new diagnostic and treatment strategies. Recent advances in non-coding RNAs have opened up new avenues for research, including circular RNAs (circRNAs) as molecules that play a multifaceted role in cellular processes. Research into circRNAs revealed their unique structure, characterized by the covalent formation of a closed loop, thereby distinguishing them from their linear counterparts. These circRNAs are involved in regulating various aspects of cell physiology with a particular focus on cell growth and development. Interestingly, circRNAs have context-dependent functions, acting both as promoters and inhibitors of oncogenic processes, depending on the complex cellular environment in which they operate. Recent studies have identified aberrant expression patterns of circRNAs in the context of cervical cancer, implying their key role in the disease development. The different expression profiles of circRNAs associated with cervical cancer offer promising opportunities for early detection, accurate prognosis assessment, and personalized treatment strategies. The presented comprehensive review offers an in-depth study of cervical cancer-associated circRNAs, their specific functions and complex molecular mechanisms driving the onset and progression of cervical cancer. Increasing evidence suggests that circRNAs can serve as invaluable biomarkers for early detection of cervical cancer and promising therapeutic targets for intervention. Delving into the complex interaction between circRNAs and cervical cancer paves the way for innovative and personalized approaches to combat this serious disease, aiming at reducing its impact on women’s health worldwide and improve patient outcomes. Unraveling the mysteries of circRNAs in the context of cervical cancer makes the prospects for a breakthrough in its diagnosis and treatment more promising.